Microbially influenced corrosion and rust tubercle formation on sheet piles in freshwater systems - Annika Fiskal; Jeremiah Shuster; Stefan Fischer; Prachi Joshi; Lipi Raghunatha Reddy; Sven‐Erik Wulf; Andreas Kappler; Helmut Fischer; Ilona Herrig; Jutta Meier (Environmental Microbiology, 2023)
The extent of how complex natural microbial communities contribute to metal corrosion is still not fully resolved, especially not for freshwater environments. In order to elucidate the key processes, we investigated rust tubercles forming massively on sheet piles along the river Havel (Germany) applying a complementary set of techniques. In‐situ microsensor profiling revealed steep gradients of O 2 , redox potential and pH within the tubercle. Micro‐computed tomography and scanning electron microscopy showed a multi‐layered inner structure with chambers and channels and various organisms embedded in the mineral matrix. Using Mössbauer spectroscopy we identified typical corrosion products including electrically conductive iron (Fe) minerals. Determination of bacterial gene copy numbers and sequencing of 16S rRNA and 18S rRNA amplicons supported a densely populated tubercle matrix with a phylogenetically and metabolically diverse microbial community. Based on our results and previous models of physic(electro)chemical reactions, we propose here a comprehensive concept of tubercle formation highlighting the crucial reactions and microorganisms involved (such as phototrophs, fermenting bacteria, dissimilatory sulphate and Fe(III) reducers) in metal corrosion in freshwaters.